2008
DOI: 10.1093/hmg/ddn262
|View full text |Cite
|
Sign up to set email alerts
|

Gene-environment interactions in the causation of neural tube defects: folate deficiency increases susceptibility conferred by loss of Pax3 function

Abstract: Risk of neural tube defects (NTDs) is determined by genetic and environmental factors, among which folate status appears to play a key role. However, the precise nature of the link between low folate status and NTDs is poorly understood, and it remains unclear how folic acid prevents NTDs. We investigated the effect of folate level on risk of NTDs in splotch (Sp(2)(H)) mice, which carry a mutation in Pax3. Dietary folate restriction results in reduced maternal blood folate, elevated plasma homocysteine and red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
138
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(153 citation statements)
references
References 44 publications
12
138
3
Order By: Relevance
“…Lack of dietary FA produces profound retardation in embryonic growth and developmental progression, suggesting that cell proliferation is compromised (21). In our previous work (13), we found that neural crest cells from open neural tubes of Sp Ϫ/Ϫ embryos failed to form neurospheres in culture.…”
Section: Discussionmentioning
confidence: 70%
“…Lack of dietary FA produces profound retardation in embryonic growth and developmental progression, suggesting that cell proliferation is compromised (21). In our previous work (13), we found that neural crest cells from open neural tubes of Sp Ϫ/Ϫ embryos failed to form neurospheres in culture.…”
Section: Discussionmentioning
confidence: 70%
“…In addition, folate deficiency increases uracil mis-incorporation into DNA in mice, which could lead to genomic instability. 7 Genomic instability and changes in DNA methylation status may, therefore, have significant effects on the development of NTDs.…”
Section: Introductionmentioning
confidence: 99%
“…Twsg1 2/2 mice do not show NTDs, indicating the dispensability of TWSG1 for neural tube development. The protective effect of methyl donors on NTD development was previously established in both NTD-susceptible mice (17,71,72) and humans (2,3,7). In contrast to the effect of methyl donor supplementation, increased parity may act to favor NTDs, based on work in humans (33).…”
Section: Figure 2 Parity Increases Defects In Twsg1mentioning
confidence: 99%
“…In each stage, 3 factors are considered for their inferred effects: deficiency of TWSG1, MDS, and increased parity. Grayed factors in the first neural tube step indicate this portion of the model is derived from literature review and not from the results of this study: MDS references (2,3,7,17,71,72); parity reference (33). MDS, methyl donor supplemented.…”
Section: Figure 2 Parity Increases Defects In Twsg1mentioning
confidence: 99%